Communications [Technology 2000 analysis and forecast]. - Riezenman, M.J.
The mergers and acquisitions on-going among communications companies around the world fall mostly into two categories. Some deals involve similar companies-two cellular service providers, say, seeking to plug gaps in their coverage footprints and to cut costs by reducing churn, eliminating roaming charges, and coordinating the purchase of handsets and other equipment. Others involve complementary companies-perhaps a long-distance carrier and a local service provider looking to increase revenue by bundling their services, selling them to a larger customer base, and together creating new services. Amidst all the merger frenzy, one thing that the key players and some of their larger customers have discovered is IP telephony-that is, packet-switched telephony running over a network that uses the Internet Protocol. The strategy of running voice and data traffic on the same network could both cut communications costs and make new services possible. But, for the Internet itself, those goals will not be reached without some serious tradeoffs, of which voice quality and privacy loom largest. With all the attention that cellular companies are now getting, wireless communication has also become a hot commodity. Ubiquitous connectivity seems to be envisioned in which people will always be able to communicate with each other and with the Internet, though perhaps not always with high bandwidth
Keywords: IP telephony; Internet Protocol; Acquisitions; Cellular companies; Cellular service providers; Communications companies; Local service provider; Long-distance carrier; Mergers; Packet-switched telephony; Privacy; Quality of service; Roaming charges elimination; Satellite communication; Services bundling; Technology forecast; Voice quality; Wireless communication